2015
DOI: 10.17116/terarkh201587317-22
|View full text |Cite
|
Sign up to set email alerts
|

New ideas on the therapeutic effect of a combination of vaccines against pneumococcal, Haemophilus influenzae type b infection, and influenza in patients with chronic obstructive pulmonary disease

Abstract: РезюмеЦель исследования. Оценить параметры терапевтического эффекта сочетанной вакцинации против пневмококковой, гемофильной типа b инфекций и гриппа у пациентов с хронической обструктивной болезнью легких (ХОБЛ). Материалы и методы. Проведены клиническое, бактериологическое, иммунологическое исследования в сочетании с определением показателей качества жизни (КЖ) у больных ХОБЛ в течение года после комбинированной вакцинации против пневмококковой, гемофильной типа b инфекции и гриппа. Результаты. Через 1 год п… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…While most evidence for the benefits of vaccination in COPD patients comes from studies in higher-income countries, studies looking specifically at LMICs have also found that influenza vaccination is beneficial and cost-effective [108]. The benefits of a comprehensive vaccination program can be substantial: one Russian study in patients with COPD found combination vaccination against pneumococcal infection, Haemophilus influenza type b infection, and influenza resulted in a 3.7-fold reduction in COPD exacerbations and a 3.4-fold decrease in antibiotic use in the year-long followup period [109].…”
Section: Beyond Infectious Diseasevaccination As An Important Tool Fomentioning
confidence: 99%
“…While most evidence for the benefits of vaccination in COPD patients comes from studies in higher-income countries, studies looking specifically at LMICs have also found that influenza vaccination is beneficial and cost-effective [108]. The benefits of a comprehensive vaccination program can be substantial: one Russian study in patients with COPD found combination vaccination against pneumococcal infection, Haemophilus influenza type b infection, and influenza resulted in a 3.7-fold reduction in COPD exacerbations and a 3.4-fold decrease in antibiotic use in the year-long followup period [109].…”
Section: Beyond Infectious Diseasevaccination As An Important Tool Fomentioning
confidence: 99%